ON UNUSUAL DEEP-VIOLET MICROCRYSTALS OF DIAMONDS FROM PLACERS OF UKRAINE - Taran M.N.; Kvasnytsya V.M.; Langer K. (My University, 2004)
A distinctive feature of Ukrainian deep-violet diamond microcrystals is a broad absorption band centered at about 560 nm (17850cm(-1) or 2.21 eV). In the Ukrainian samples, the intensity of this band is almost two orders of magnitude greater than in a light-rose diamond from Yakutia. Previously (Taran et al., 1998), the band was attributed to the N-V center because the absorption spectrum of the negative N-V center in irradiated and annealed type Ib diamonds is known to have an absorption band with a maximum at a similar wavelength. However, this assignment is not confirmed by vibrational spectroscopy and low temperature optical absorption spectroscopy in all crystals studied. In addition, at similar to77 K the band 17850 cm(-1) displays no fine structure that unambiguously evidences that it can not be the band at similar to2.2 eV, commonly attributed to the N-V center.
Keywords: diamond